Pengaruh Promosi Jabatan dan Gaya Komunikasi terhadap Kinerja Karyawan di Metro Fried Chicken Cabang Pangkalpinang - Muhammad Alifa Bintang Defana; Antonio Lisiadi; Muhammad Haikal Faran Fajri; Sultan Ilhamsyah (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study was conducted to examine the effect of job promotion and communication style on employee performance at Metro Fried Chicken Pangkalpinang branch. Quantitative method with multiple linear regression analysis was applied to determine the correlation and influence of the two variables simultaneously and partially. The results showed that job promotion and communication style have a positive and significant effect on employee performance, with an R-squared value of 0.895 which indicates that 89.5% of variations in employee performance can be explained by these two variables. These findings contribute to the development of human resource management, especially in improving employee performance with fair promotions and effective communication. It is recommended that companies pay attention to aspects of promotion fairness and improve the quality of leadership communication to achieve optimal performance.